Sex differences in opioid use and medical issues during buprenorphine/naloxone treatment - Barbosa-Leiker, Celestina (Am J Drug Alcohol Abuse, 2018)
BACKGROUND: There are sex differences in buprenorphine/naloxone clinical trials for opioid use. Whereas women have fewer opioid-positive urine samples, relative to men, a significant decrease in opioid-positive samples was found during treatment for men, but not women. In order to inform sex-based approaches to improve treatment outcomes, research is needed to determine if opioid use, and predictors of opioid use, differs between men and women during treatment. OBJECTIVES: To test for sex differences in opioid use during a buprenorphine/naloxone clinical trial and determine if sex differences exist in the associations between addiction-related problem areas and opioid use over the course of the trial. METHOD: This secondary data analysis of the National Drug Abuse Treatment Clinical Trials Network (CTN) 0003 examined sex differences (men=347, women=169) in opioid-positive samples in a randomized clinical trial comparing 7-day vs. 28-day buprenorphine/naloxone tapering strategies. Addiction-related problem areas were defined by Addiction Severity-Lite (ASI-L) domain composite scores. RESULTS: Women were more likely than men to use opioids during the course of the buprenorphine/naloxone clinical trial (B=.33, p=.01) and medical issues were positively related to submitting an opioid-positive sample during treatment for women (B=1.67, p=.01). No ASI-L domain composite score was associated with opioid-positive samples during treatment for men. CONCLUSION: Women were more likely than men to use opioids during the course of the buprenorphine/naloxone clinical trial, and medical issues predicted opioid use during treatment for women but not men. Complementary treatment for medical problems during opioid replacement therapy may benefit women.